Neuropharmacology of Alcohol Addiction with Special Emphasis on Proteomic Approaches for Identification of Novel Therapeutic Targets - Ray, Suman K.; Mukherjee, Sukhes (Current Neuropharmacology, 2023)
Alcohol is a generic pharmacological agent with only a few recognized primary targets. Nmethyl- D-aspartate, gamma-aminobutyric acid, glycine, 5-hydroxytryptamine 3 (serotonin), nicotinic acetylcholine receptors, and L-type Ca2+ channels and G-protein-activated inwardly rectifying K channels are all involved. Following the first hit of alcohol on specific brain targets, the second wave of indirect effects on various neurotransmitter/neuropeptide systems begins, leading to the typical acute behavioral effects of alcohol, which range from disinhibition to sedation and even hypnosis as alcohol concentrations rise. Recent research has revealed that gene regulation is significantly more complex than previously thought and does not fully explain changes in protein levels. As a result, studying the proteome directly, which differs from the genome/transcriptome in terms of complexity and dynamicity, has provided unique insights into extraordinary advances in proteomic techniques that have changed the way we can analyze the composition, regulation, and function of protein complexes and pathways underlying altered neurobiological conditions. Neuroproteomics has the potential to revolutionize alcohol research by allowing researchers to gain a better knowledge of how alcohol impacts protein structure, function, connections, and networks on a global scale. The amount of information collected from these breakthroughs can aid in identifying valuable biomarkers for early detection and improved prognosis of an alcohol use disorder and future pharmaceutical targets for the treatment of alcoholism.
Keywords: neuroproteomics